Time spent outside of target glucose range for young children with type 1 diabetes: a continuous glucose monitor study. Issue 8 (17th March 2020) - DiMeglio, L. A.; Kanapka, L. G.; DeSalvo, D. J.; Anderson, B. J.; Harrington, K. R.; Hilliard, M. E.; Laffel, L. M.; Tamborlane, W. V.; Van Name, M. A.; Wadwa, R. P.; Willi, S. M.; Woerner, S.; et al.
Abstract: Aim: To assess the associations between demographic and clinical characteristics and sensor glucose metrics in young children with type 1 diabetes, using masked, continuous glucose monitoring data from children aged 2 to < 8 years. Research design and methods: The analysis included 143 children across 14 sites in the USA, enrolled in a separate clinical trial. Eligibility criteria were: age 2 to <8 years; type 1 diabetes duration ≥3 months; no continuous glucose monitoring use for past 30 days; and HbA1c concentration 53 to <86 mmol/mol (7.0 to <10.0%). All participants wore masked continuous glucose monitors up to 14 days. Results: On average, participants spent the majority (13 h) of the day in hyperglycaemia (>10.0 mmol/l) and a median of ~1 h/day in hypoglycaemia (<3.9 mmol/l). Participants with minority race/ethnicity and higher parent education levels spent more time in target range, 3.9–10.0 mmol/l, and less time in hyperglycaemia. More time in hypoglycaemia was associated with minority race/ethnicity and younger age at diagnosis. Continuous glucose monitoring metrics were similar in pump and injection users. Conclusions: Given that both hypo‐ and hyperglycaemia negatively impact neurocognitive development, strategies to increase time in target glucose range for young children are needed. What's new?: Traditional type 1 diabetes management in young children has focused on avoiding hypoglycaemia even at the expense of hyperglycaemia. There are limited glucose profile data available for very young children with type 1 diabetes. Very young children with type 1 diabetes spend the majority of the day outside of the target glucose range. Given that both hypo‐ and hyperglycaemia negatively impact paediatric neurocognitive development, strategies to increase time in target glucose range are needed.